Water quality. Detection and enumeration of Escherichia Coli and coliform bacteria in surface and waste water. Miniaturized method (most probable number) for the detection and enumeration of $7IE. coli$7R in surface and waste water Part 3, (15th July 2001) - British Standards Institution,
No abstract available